PENGARUH FLEXIBLE WORKING ARRANGEMENT DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS: ANALISIS PADA KARYAWAN KCP BANK SYARIAH INDONESIA DI JAKARTA - Ratono; Efnu Munanda; Agung Surya Dwianto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
The purpose of this research is to analyze how strong flexible working arrangements and job satisfaction affect employee productivity at KCP Bank Syariah Indonesia in Jakarta. Flexible working arrangements allow for flexibility in working hours, task allocation, and remote work. Job satisfaction and employee productivity are crucial for the success of a company. The method used is an associative quantitative method with primary data sources. The technical analysis used in this research is multiple regression analysis techniques. The population in the study is KCP BSI employees in Jakarta. Samples were collected by distributing questionnaires through social networks. The data obtained from 100 respondents at Bank Syariah Indonesia were then compiled in tabular form and processed using SPSS. The results of this research indicate that flexible working arrangements increase employee productivity and job satisfaction increases work productivity. These results show that increasing employee productivity can be achieved through flexible work arrangements and employee job satisfaction. More than 50% of the variation in job satisfaction and productivity can be explained by the variables in this study. This study is useful for businesses, especially Bank Syariah Indonesia, to create more flexible strategies and make employees happier in the workplace. In addition, this shows a positive relationship between work flexibility and productivity. This can be the basis for company decisions to develop more flexible work arrangements. Keywords: Flaxible Working Arrangement, Job Satisfaction, Productivity